Cellulose Depolymerization over Heterogeneous Catalysts - Shrotri, Abhijit; Kobayashi, Hirokazu; Fukuoka, Atsushi (Accounts of chemical research, 2018)
Cellulosic biomass is the largest source of renewable organic carbon on our planet. Cellulose accounts for 40–50 wt % of this lignocellulose, and it is a feedstock for industrially important chemicals and fuels. The first step in cellulose conversion involves its depolymerization to glucose or to its hydrogenated product sorbitol. The hydrolysis of cellulose to glucose by homogeneous mineral acids was the subject of research for almost a century. However, homogeneous acids have significant drawbacks and are neither economical nor environmentally friendly. In 2006, our group reported for the first time the ability of heterogeneous catalysts to depolymerize cellulose through hydrolytic hydrogenation to produce sorbitol. Later, we reported the hydrolysis of cellulose to glucose using carbon catalyst containing weakly acidic functional groups. Understanding the reaction between cellulose and heterogeneous catalyst is a challenge as the reaction occurs between a solid substrate and a solid catalyst. In this Account, we describe our efforts for the conversion of cellulose to sorbitol and glucose using heterogeneous catalysts. Sorbitol is produced by sequential hydrolysis and hydrogenation of cellulose in one pot. We reported sorbitol synthesis from cellulose in the presence of supported metal catalysts and H2 gas. The reducing environment of the reaction prevents byproduct formation, and harsh reaction conditions can be used to achieve sorbitol yield of up to 90%. Glucose is produced by acid catalyzed hydrolysis of cellulose, a more challenging reaction owing to the tendency of glucose to rapidly decompose in hot water. Sulfonated carbons were first reported as active catalysts for cellulose hydrolysis, but they were hydrothermally unstable under the reaction conditions. We found that carbon catalysts bearing weakly acidic functional groups such as hydroxyl and carboxylic acids are also active. Weakly acidic functional groups are hydrothermally stable, and a soluble sugar yield of 90% was achieved in a 20 min reaction. We clarified that the polycyclic aromatic surface of the carbon adsorbs cellulose molecules on its surface by CH−π and hydrophobic interactions driven by a positive change in entropy of the system. The adsorbed molecules are rapidly hydrolyzed by active sites containing vicinal functional groups that recognize the hydroxyl groups on cellulose to achieve a high frequency factor. This phenomenon is analogous to the hydrolysis of cellulose by enzymes that use CH−π and hydrophobic interactions along with weakly acidic carboxylic acid and carboxylate pair to catalyze the reaction. However, in comparison with enzymes, carbon catalyst is functional over a wide range of pH and temperatures. We also developed a continuous flow slurry process to demonstrate the feasibility for commercial application of carbon-catalyzed cellulose hydrolysis to glucose using inexpensive catalyst prepared by air oxidation. We believe that further efforts in this field should be directed toward eliminating roadblocks for the commercialization of cellulose conversion reactions.